Microstructural development for optimum fracture toughness of Al2O3-3YSZ composites. Issue 4 (2nd October 2022) - Salma, U.; Rafferty, A.; Hasanuzzaman, M.
ABSTRACT: Alumina-based ceramics are widely used for making wear-resistant components and machine parts due to their high hardness, strength, wear-resistance, and high chemical and thermal stability. However, low fracture toughness (KIC 3.0 MPa.m 1/2 ) inhibits alumina's usage where high toughness is a pre-requisite (e.g. ceramic engines). In this work, yttria-stabilised zirconia (3YSZ) was added to alumina and a two-step sintering process was used to make a composite with enhanced mechanical properties. The key properties – hardness, fracture toughness, and percentage theoretical density (Dth ) – could be related to microstructural features. It was revealed that higher numbers of elongated grains formed with increasing additions of 3YSZ. The maximum fracture toughness and hardness achieved were 5.51 MPa.m 1/2 and 10.96 GPa, respectively, for the Al2 O3 -30 wt% 3YSZ composite, believed mainly due to the high proportion of elongated grains. The best-performing sample had a density of 96.1% Dth and the average grain size was 0.35 µm. The thermal expansion coefficient was measured as 6.5 × 10 −6 K −1 .